Development of customer driven activity - based costing model for manufacturing company [electronic resource] - 445066 Lee, Hsiao Mun (2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2007